Con: Liver transplantation for expanded criteria malignant diseases. Issue 1 (21st December 2017) - Schaefer, Benedikt; Zoller, Heinz; Schneeberger, Stefan
Abstract : Organ shortage requires policies and guidelines to aid organ allocation along the principles of urgency or utility. Identifying patients with significant benefit and withholding liver transplantation (LT) from patients too sick for transplantation are ongoing challenges, in particular in patients with malignancies. An arbitrary threshold of >50% 5‐year overall survival (OS) is broadly considered a minimum standard for LT. In patients transplanted for intrahepatic cholangiocarcinoma (iCC), this was only achieved in select cases and when the tumor had a diameter of <2 cm. In patients with extrahepatic and hilar cholangiocarcinoma (CCC), strict selection criteria and combined preoperative radiotherapy/chemotherapy according to the Mayo protocol showed that acceptable longterm results can be achieved in a single high‐volume center but are difficult to repeat elsewhere. Furthermore, only rigorously selected patients with neuroendocrine tumors (NETs) meeting the NET Milan criteria adopted by United Network for Organ Sharing can also have >50% 5‐year OS. A prospective study in patients with unresectable colorectal cancer metastases in the liver has shown promising OS rates, but further prospective trials are warranted. Current evidence shows that none of the proposed expanded malignant criteria justify deviation of scarce donor organs to patients with hilar CCC, iCC > 2 cm, metastatic NET beyond NET Milan criteria, or metastatic colorectal cancer (CRC) outside clinical trials. Liver Transplantation 24 104–111 2018 AASLD.